East Kalimantan Madrasah Teachers’ Perception of Religious Moderation - Anwaril Hamidy; Yunita Noor Azizah; Bambang Iswanto (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Efforts to strengthen religious moderation in the madrasah environment are strongly influenced by the madrasah teacher's perception of religious moderation. It relates to the extent of the socialization of religious moderation to madrasah teachers. The study aims to describe the socialization of religious moderation to madrasah teachers in East Kalimantan and their perceptions of the importance of religious moderation for students. An online survey was conducted of 73 madrasah teachers in East Kalimantan. The survey consists of two close-ended questions and one open-ended question. The answers of close-ended questions were processed and presented descriptively. The answers of open-ended questions were analyzed through the stages of reduction, data presentation and conclusions. The results showed that the majority of respondents (78%) have participated in socialization about religious moderation. Most respondents (91%) also agree that religious moderation is important for students. The reasons for the importance of religious moderation for students are to foster student tolerance, maintain the integrity of the nation, prevent extreme religious attitudes, adequate to the needs of the era, part of the obligatory of Allah SWT and so that students do not dichotomize between religious knowledge and general science. Even so, there are still teachers who doubt the importance of religious moderation for students. Therefore, efforts are needed to strengthen sustainable religious moderation in order to realize a common perception of religious moderation in the madrasah environment.